2016
DOI: 10.1371/journal.pone.0168316
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study Reveals the PLAG1 Gene for Knuckle, Biceps and Shank Weight in Simmental Beef Cattle

Abstract: Carcass traits of beef cattle have been genetically improved to increase yield of high quality meat. Genome-wide association study (GWAS) is a powerful method to identify genetic variants associated with carcass traits. For the 770K genotyped SNPs from 1141 Chinese Simmental cattle, we used the compressed mixed linear model (CMLM) to perform a genome-wide association study for knuckle, biceps and shank of beef carcass traits. Seventeen significantly associated SNPs were found, which are located on BTA6, BTA14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 37 publications
0
33
1
Order By: Relevance
“…This region contains several widely known and well described genes, including the zinc finger protein Pleomorphic adenoma gene 1 ( PLAG1 ) gene. This region is of interest as previous GWAS studies have found significant associations between the PLAG1 gene, including surrounding genes, to have important associations with stature 30 , fertility 26 and beef production traits, such as carcass weight 26,3133 . In the study by Fortes et al .…”
Section: Resultsmentioning
confidence: 99%
“…This region contains several widely known and well described genes, including the zinc finger protein Pleomorphic adenoma gene 1 ( PLAG1 ) gene. This region is of interest as previous GWAS studies have found significant associations between the PLAG1 gene, including surrounding genes, to have important associations with stature 30 , fertility 26 and beef production traits, such as carcass weight 26,3133 . In the study by Fortes et al .…”
Section: Resultsmentioning
confidence: 99%
“…The XKR4 was associated with subcutaneous rump fat thickness, scrotal circumference, serum concentration of prolactin, and sexual precocity (Fortes et al, 2012a;Porto Neto et al, 2012;Bastin et al, 2014;Takada et al, 2018). PLAG1 has been implicated in the regulation of stature and weight (Littlejohn et al, 2012;Pryce et al, 2012;Song et al, 2016). This gene was associated with yearling weight in Australian Tropical Composite breeds (Porto-Neto et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The HEPACAM2 gene was previously identified in a QTL region for mid-test metabolic weight (MMWT) in SimAngus on BTA4 [ 48 ]. The CHCHD7 gene on BTA14 is associated with CWT in the Hanwoo breed [ 11 ], with knuckle, biceps and shank trait in Chinese Simmental cattle [ 49 ], with carcass weight in Japanese Black steers [ 50 ], with back fat thickness and rump fat thickness in the Nellore breed [ 51 ], and with fat thickness and intramuscular fat in composite cattle [ 52 ]. The UBXN2B gene is associated with MMWT in SimAngus [ 48 ], and with carcass weight, carcass fat, and carcass conformation in Simmental [ 53 ].…”
Section: Discussionmentioning
confidence: 99%